[4+1] Cycloaddition of Enaminothiones and Aldehyde N‐Tosylhydrazones Toward 3‐Aminothiophenes. Issue 22 (8th October 2018) - Liu, Zhuqing; Wu, Ping; He, Yuan; Yang, Ting; Yu, Zhengkun
Abstract: An efficient protocol toward trisubstituted 3‐aminothiophenes has been developed through a [4+1] cycloaddition of enaminothiones and aldehyde N ‐tosylhydrazones under transition‐metal‐free conditions. 3‐Aminothiophene derivatives as well as their chiral analogs were obtained in good to excellent yields. Direct interaction of the enaminothiones with the diazo compounds of α ‐carbonyl or ester group‐functionalized aldehydes also efficiently afforded the same type of 3‐aminothiophenes. The diversity of the synthetic methodology has been demonstrated by the broad substrate scopes and excellent chemoselectivity in cleavage of the C−S, C−O, and C−N bonds in enaminothiones. Abstract :